ASIAB Chatbot for Disaster Mitigation Learning at Madrasah Ibtidaiyah - Nisrina Hikmawati (Department of Geography Education, University of Jember, 2024)
Learning Disaster mitigation in schools is an essential concern of the government in forming a character of preparedness and resilience for students to face disasters. According to technological developments, adequate learning media is also important for independent learning. Therefore, this study aimed to develop disaster mitigation learning media for Madrasah Ibtidaiyah (Islamic Elementary School) students using AI chatbot technology. The Research and Development method with the ADDIE model was adopted, consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The product was validated by media and material experts as excellent, with percentages of 98.3% and 93.95% respectively. Product validation was carried out using questionnaires, while assessments were based on several indicators, namely attractive, easy-to-understand, technical standards, and material suitability. Furthermore, practicality and effectiveness tests were conducted on teachers and students, with scores above 80%, suggesting very good usability. Practical and effective indicators were based on attractiveness, ease of use, increased motivation, and ease of assessment. In conclusion, The ASIAB chatbot was found to be highly suitable for learning by providing an innovative method to disaster mitigation education through the integration of AI chatbot technology. In addition, the ASIAB chatbot provided a validated and reliable tool that meets high standards of usability and educational effectiveness, as evidenced by high validation scores from both media and material experts. This technology also showed practicality and effectiveness in real classroom settings, thereby providing a scalable solution that can be implemented widely to enhance disaster preparedness education across Indonesian schools.